2011
DOI: 10.1002/pmic.201100114
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of oil bodies isolated from the unicellular green microalga Chlamydomonas reinhardtii: With focus on proteins involved in lipid metabolism

Abstract: Oil bodies are sites of energy and carbon storage in many organisms including microalgae. As a step toward deciphering oil accumulation mechanisms in algae, we used proteomics to analyze purified oil bodies from the model microalga Chlamydomonas reinhardtii grown under nitrogen deprivation. Among the 248 proteins (≥ 2 peptides) identified by LC-MS/MS, 33 were putatively involved in the metabolism of lipids (mostly acyl-lipids and sterols). Compared with a recently reported Chlamydomonas oil body proteome, 19 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
203
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(211 citation statements)
references
References 33 publications
7
203
1
Order By: Relevance
“…Previous studies have provided evidence for fatty acid recycling, and this is consistent with increased expression of lipases in nitrogen-starved cells (18,42,73). Some of these are annotated as TAG lipases, which would be counterintuitive, but they may well be membrane lipid lipases that release fatty acids that are subsequently incorporated into TAGs.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Previous studies have provided evidence for fatty acid recycling, and this is consistent with increased expression of lipases in nitrogen-starved cells (18,42,73). Some of these are annotated as TAG lipases, which would be counterintuitive, but they may well be membrane lipid lipases that release fatty acids that are subsequently incorporated into TAGs.…”
Section: Discussionsupporting
confidence: 54%
“…Surprisingly, genes LIPG2, Cre05.g234800, and Cre02.g127300, encoding candidate TAG lipases, are up-regulated, which has also been noted in previous transcriptome and proteome studies (18,42). One possibility is that these enzymes are not TAG lipases but rather play a role in releasing fatty acids from membrane lipids for de novo TAG synthesis.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…MLDP stabilizes mature LDs and acts as a recruiting platform for other proteins and enzymes required for the maturation of LDs. In C. reinhardtii, MLDP is identified as an abundant protein on the outer surface of the LDs proteome (Moellering and Benning, 2010;Nguyen et al, 2011). MLDP abundance positively correlates with the accumulation of TAGs (Tsai et al, 2014).…”
mentioning
confidence: 99%
“…with structural similarities to other OB-associated proteins (Vieler et al, 2012), and a major lipid droplet protein was also identified in Chlamydomonas reinhardtii and other green algae species (Moellering and Benning, 2010;Peled et al, 2011). Proteomic analysis in different plants and algae identified a wide variety of proteins associated with OBs (Katavic et al, 2006;Jolivet et al, 2009;Nguyen et al, 2011;Tnani et al, 2011Tnani et al, , 2012. Different roles have been proposed to the OB-associated proteins, including OB biogenesis, stability, trafficking, and mobilization.…”
mentioning
confidence: 99%